Magneto-optical Kerr effect characterization of a uniform nanocrystalline Fe3O4 monolayer fabricated on a silicon substrate functionalized with catechol groups. Issue 6 (18th January 2016) - Hojo, Daisuke; Suzuki, Kazuya Z.; Mizukami, Shigemi; Adschiri, Tadafumi
Abstract : Magneto-optical devices can be fabricated by printing magnetic nanocrystals on a catechol-group-functionalized substrate; the process is macroscopically monolayer controlled. Abstract : Magneto-optical Kerr effect (MOKE) measurements were performed on a monolayer of oleic-acid-modified Fe3 O4 nanocrystals chemically adsorbed on a catechol-group-functionalized Si substrate. By functionalizing the substrate with catechol groups that have a high affinity for Fe3 O4 and form chemical bonds in exchange for the oleic acid, a magnetic nanocrystalline monolayer with a sufficiently high coverage could be fabricated uniformly on the macroscopic scale. After the completion of the organic-molecule-directed self-assembly process and subsequent rinsing with a dispersing solvent, only a monolayer of chemisorbed nanocrystals remained on the substrate. This resulted in the substrate exhibiting uniform MOKE signals on the macroscopic scale. The monolayer synthesis technique developed in this study should lead to the fabrication of printable MOKE devices.